Nursing students' self-efficacy in providing transcultural care - Lim, J.; Downie, Jill; Nathan, Pauline (Elsevier Ltd., 2004)
The aim of any health care service is to provide optimal quality care to clients and families regardless of their ethnic group. As today's Australian society comprises a multicultural population that encompasses clients with different cultural norms and values, this study examined undergraduate nursing students' self-efficacy in providing transcultural nursing care. A sample of 196 nursing students enrolled in the first and fourth year of a pre-registration nursing program in a Western Australian University were invited to participate in a survey incorporating a transcultural self-efficacy tool (TSET) designed by Jeffery [Unpublished instrument copyrighted by author, 1994]. The findings revealed that fourth year students, exposed to increased theoretical information and clinical experience, had a more positive perception of their self-efficacy in providing transcultural nursing skills than the first year students. In addition, the study found that age, gender, country of birth, languages spoken at home and previous work experience did not influence the nursing students' perception of self-efficacy in performing transcultural care. The study supports the notion that educational preparation and relevant clinical experience is important in providing nursing students with the opportunity to develop self-efficacy in performing effective and efficient transcultural nursing in today's multicultural health care system. It is for this reason that educators need to focus on providing students with relevant theoretical information and ensure sufficient clinical exposure to support student learning in the undergraduate program.